S3 Guideline for Chronic Pancreatitis – Diagnosis, Classification and Therapy for the Radiologist - Schreyer, A. G.; Jung, M.; Riemann, J. F.; Niessen, C.; Pregler, B.; Grenacher, L.; Hoffmeister, A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Chronic pancreatitis shows an increasing prevalence and incidence mainly in the Western Hemisphere. Early diagnosis and therapy are frequently delayed because of non-specific symptoms as well as non-specific blood values. The German Society of Digestive and Metabolic Diseases (DGVS) organized the preparation and publication of an interdisciplinary S3 level guideline with the support of the German Radiological Society (DRG) as 1 of 11 contributing societies. In this article we present and discuss the main topics of the guideline regarding the diagnosis, differential diagnosis and therapy of complications of this complex chronic disease with a focus on clinical and scientific radiologists.Key Points:• Ultarsound represents the perfect first line imaging modality • For further diagnostic werk up MRI with MRCP are recommended for the differential diagnosis of pancreatic cancer • For clinical studies the modified (CT, MRI) Cambridge classification is recommendedCitation Format:• Schreyer AG, Jung M, Riemann JF et al. S3 Guideline for Chronic Pancreatitis – Diagnosis, Classification and Therapy for the Radiologist. Fortschr Röntgenstr 2014; 186: 1002 – 1008
Keywords: pancreas; CT; pancreatitis; MR imaging